2017
DOI: 10.1111/plb.12568
|View full text |Cite
|
Sign up to set email alerts
|

Long‐distance movement of phosphate starvation‐responsive microRNAs in Arabidopsis

Abstract: Plant microRNAs are small RNAs that are important for genetic regulation of processes such as plant development or environmental responses. Specific microRNAs accumulate in the phloem during phosphate starvation, and may act as long-distance signalling molecules. We performed quantitative PCR on Arabidopsis hypocotyl micrograft tissues of wild-type and hen1-6 mutants to assess the mobility of several phosphate starvation-responsive microRNA species. In addition to the previously confirmed mobile species miR399… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…The read abundance of miR2111–1 and its target transcript were greater in the stems and roots than in the leaves, in agreement with the expression pattern of miR2111 and its target in Arabidopsis and B. napus [7, 9]. The presence of miR2111 in the stem tissue of N. benthamiana raised the possibility that it acts as a long-distance miRNA, like miR399 [32]; however miR2111 does not appear to be mobile in Arabidopsis [47]. The abundance of the F-box transcript in this study did not decrease during -P in N. benthamiana (Additional file 2: Figure S3); this was also the case for Arabidopsis, where miR2111 and the F-box transcript abundance both increased under phosphate starvation [7].…”
Section: Discussionsupporting
confidence: 59%
“…The read abundance of miR2111–1 and its target transcript were greater in the stems and roots than in the leaves, in agreement with the expression pattern of miR2111 and its target in Arabidopsis and B. napus [7, 9]. The presence of miR2111 in the stem tissue of N. benthamiana raised the possibility that it acts as a long-distance miRNA, like miR399 [32]; however miR2111 does not appear to be mobile in Arabidopsis [47]. The abundance of the F-box transcript in this study did not decrease during -P in N. benthamiana (Additional file 2: Figure S3); this was also the case for Arabidopsis, where miR2111 and the F-box transcript abundance both increased under phosphate starvation [7].…”
Section: Discussionsupporting
confidence: 59%
“…Using the same approach of wild-type-hen1 micrografting, another study further showed that, in addition to miR399, the corresponding near-complementary miR399* species was graft-transmissible between shoots and roots. The analysis also revealed that miR827 and miR2111 were capable of long-distance movement, while their respective miRNA* species were not, indicating that the mobility of miRNA species is selective 85 . miR2111 in the legume Lotus japonicus has also been found to undergo shoot-to-root long-distance translocation to regulate rhizobial infection.…”
Section: Mobile Small Rnas: Sirnas and Mirnasmentioning
confidence: 99%
“…However, since most of the mRNAs are expressed in mesophyll cells, it is unclear how they could enter the phloem stream in the apoplasmic loader A. thaliana . In addition to those many phloem-mobile proteins and mRNAs, the role of microRNAs 87 and lipids 88 as systemic signals needs to be further explored.…”
Section: Phloem Transportmentioning
confidence: 99%